Manejo sanitario en la producción de rumiantes menores - Flores Alvario, Tony Manuel (2023)
Sanitary management in the production of small ruminants is essential to ensure the health and welfare of these animals, but also has a significant economic impact. Hygiene management is essential for their health and productivity, this includes measures such as vaccination, parasite control and hygiene, healthy animals grow and reproduce better, resulting in safer and higher quality feed that ensures profitability and sustainability of livestock production. Diseases can have a significant financial impact, resulting in lost productivity, veterinary treatment costs and reduced product quality, whereby the spread of disease can also lead to animal deaths and loss of customers. Sanitation management is closely related to food safety, good hygiene management reduces the risk of foodborne diseases and ensures food safety and nutrition. Therefore, the breeding of these small ruminants is mainly focused on the gelid climate region, although it can also occur in temperate climates, although it has a greater acceptance in cold climates with 91.3 % and 93 % in its production. It should be taken into account that 25 % of the breeders use deworming of these animals, 53.4 % carry out vaccination programs to prevent diseases that can be acquired in production and 56 % of the producers carry out the corresponding cleaning of their area to avoid the presence of pathogens or other affections. Animal stress, especially heat stress, can affect health and production, so strategies such as providing shade and access to fresh water are critical, and technologies are transforming disease prevention and health management, leading to a more sustainable and protected future for these animals.